Preparation of future higher education specialists for professional self-improvement - Плахотник, О. В.; Соколовська, Ірина Анатоліївна; Гончаренко, О. М.; Юхно, Ю. О.; Цимбал, В. А.; Будагов, Р. І.; Plakhotnik, Olga; Sokolovskaya, Irina; Goncharenko, Alexander; Yukhno, Yuri; Tsymbal, Viktor; Budagov, Rasim (My University, 2021)
В оглядовій статті йдеться про процес розвитку готовності фахівця вищої школи до професійного самовдосконалення. У процесі нашого дослідження ми спиралися на розуміння професійного самовдосконалення як комплексного особистісно значимого явища, обумовленого дією спектру психологічних, соціально-економічних, культурних, фахових особистісно-орієнтованих чинників. Досліджувана нами проблема в умовах дистанційного та змішаного навчання потребує додаткового наукового обґрунтування, а також уточнення педагогічних умов формування готовності майбутніх фахівців педагогіки вищої школи до професійного самовдосконалення, визначення особистісно та контекстно орієнтованих методик підготовки майбутніх викладачів вищої школи до самовдосконалення та фахового розвитку, а також розроблення належного дидактичного, науково-методичного забезпечення, що і може складати перспективи подальшого дослідження.The scientific review considers the process of developing the readiness of future higher education specialists for professional self-improvement. The analysis and reflections on the contemporary scientific research presented in the article made it possible to present professional self-improvement as a complex phenomenon due to a range of psychological, socio-economic, cultural, professional and personal factors. Theoretical analysis of researches by domestic and foreign scientists, as well as our results, confirm the key positions of S. Rubinstein, O. Leontiev and others that the development of personality is carried out through activities. Accordingly, it is the activity approach that is defined by us as the leading one in the methodology of forming the readiness of future teachers for self-improvement and led to understanding the dynamics of this process from the standpoint of phasing changes in such types of personally significant activities as self-actualization and self-realization. realization of self-knowledge, perception of "self-image", self-organization, self-control and self-correction. In the course of our study it was found that the process of professional self-improvement of future higher education specialists depends on their personal characteristics, methodological competence and "image of professional self", ability to reflect, as well as depth and intensity of self-knowledge.
Підготовка майбутніх фахівців вищої школи до професійного самовдосконалення
Keywords: readiness for professional self-improvement; personal self-improvement; self-knowledge; self-development; self-management; self-realization; self-correction; self-creation; self-organization; Introduction; готовність до професійного самовдосконалення; особистісне самовдосконалення; самопізнання; саморозвиток; самоуправління; самореалізація; самокорекція; самотворення; самоорганізація